PROPRANOLOL-INDUCED CARDIAC DECOMPENSATION IN THYROID STORM - Suria, Mas; MA, Syazwan; KG, Goh (Journal of the ASEAN Federation of Endocrine Societies, 2024)
INTRODUCTION/BACKGROUND Propranolol is one of the preferred beta-blocking agents used in thyroid storm. It is highly lipid-soluble and effective in reducing T3 concentration up to 30% if given in high doses. However, only a few cases reported on the side effects of this drug, especially life- threatening complications in thyroid storm. We reported 4 cases of propranolol-induced circulatory collapse in patients with thyro-cardiac disease who presented with thyroid storm between 2022- 2024. CASE 1 A 28-year-old male diagnosed with Graves’ disease developed thyroid storm with cardiac decompensation post-wound debridement. He received carbimazole 30 mg and propranolol 40 mg prior to surgery. The propranolol was withheld following the unfortunate event and he recovered after 3 days. CASE 2 A 32-year-old female with Graves’ disease presented with acute heart failure and tachyarrhythmia. She was initially normotensive on arrival; however, she developed circulatory collapse after receiving propranolol 40 mg. She was managed in the ICU before succumbing to her death due to severe cardiac decompensation. CASE 3 A pregnant female at 34 weeks AOG presented with an impending thyroid storm and premature uterine contraction. She was normotensive and tachycardic on presentation. The condition was complicated by cardiogenic shock and acute heart failure right after propranolol 40 mg administration. She was placed on mechanical ventilation but had an intrauterine foetal loss. CASE 4 A 43-year-old female presented with thyroid storm and unstable atrial fibrillation. She was intubated and received synchronized cardioversion at 150 J together with antithyroid and glucocorticoid drugs. Her condition worsened after she was given oral propranolol 20 mg and she eventually succumbed due to cardiac decompensation. CONCLUSION Long-acting beta-blockers should be used with caution in thyroid storms with pre-existing thyro-cardiac disease as they can potentially impede the compensatory mechanism and consequently cause hemodynamic instability.